ANALISIS RASIO KEUANGAN UNTUK MEMPREDIKSI PERUBAHAN LABA PADA PERUSAHAAN KIMIA DI BEI - Aprilia, Fera; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is conducted in the chemical companies which are listed in the Indonesian Stock Exchange (BEI). It is aimed to find out the influence of financial ratios to the changes in profit of a company in the future. The analytical instruments are the liquidity ratio which consists of current ratio and quick ratio; solvency ratio which consists of debt to total assets ratio and the profitability ratio which consists of Net Profit Margin and Return on Equity in the forms of models to predict whether a company is heading to bankruptcy or increased profitability to the changes in profit in the chemical companies which are listed in the Indonesian Stock Exchange (IDX) in 2010-2014 periods. Based on the result of hypothesis test, it shows that: (1) Current Ratio has positive influence to the changes in profit, (2) Quick Ratio has positive influence to the changes in profit, (3) Debt to Total Assets Ratio has positive influence to the changes in profit, (4) Net Profit Margin has negative influence to the changes in profit and (5) Return on Equity has negative influence to the changes in profit.Keywords: Liquidity ratio, solvency ratio, profitability ratio, changes in profit